Radiation Doses to Patients in Interventional Coronary Procedures—Estimation of Updated National Reference Levels by Dose Audit. Issue 1 (13th September 2016) - Georges, Jean-Louis; Belle, Loic; Etard, Cécile; Azowa, Jean-Baptiste; Albert, Franck; Pansieri, Michel; Monsegu, Jacques; Barbou, Franck; Trouillet, Charlotte; Leddet, Pierre; Livarek, Bernard; Marcaggi, Xavier; et al.
Abstract: The objective of this study was to estimate the French national updated reference levels (RLs) for coronary angiography (CA) and percutaneous coronary intervention (PCI) by a dose audit from a large data set of unselected procedures and in standard-sized patients. Kerma-area product (PKA ), air kerma at interventional point (Ka, r), fluoroscopy time (FT), and the number of registered frames (NFs) and runs (NRs) were collected from 51 229 CAs and 42 222 PCIs performed over a 12-month period at 61 French hospitals. RLs estimated by the 75th percentile in CAs and PCIs performed in unselected patients were 36 and 78 Gy.cm² for PKA, 498 and 1285 mGy for Ka, r, 6 and 15 min for FT, and 566 and 960 for NF, respectively. These values were consistent with the RLs calculated in standard-sized patients. The large difference in dose between sexes leads us to propose specific RLs in males and females. The results suggest a trend for a time-course reduction in RLs for interventional coronary procedures.